Inheritance and correlations of juvenile characteristics in rubber tree clones - Gonçalves, Paulo de Souza; Vasconcellos, Maria Elizabeth C.; Valois, Afonso Celso Candeira; Silva, Edson Barcellos da (Pesquisa Agropecuaria Brasileira, 2014)
Eight characteristics in one year old clones of rubber tree (Hevea spp) were studied. The study included fourteen different clones replicated in two blocks of 25 plants per plot. The data were collected from 500 plants aproximately. Yield by a method of precocious test, total height, stem diameter, bark thickness, total number of latex vessel rings, density of latex vessels per 5 mm per ring, leaf thickness, and total number of fluxes of leaves were measured. Phenotypic and genetic correlations between the characteristics as well as heritability in the broad sense and expected gain due to selection among clones were obtained. The results showed that production is phenotypic and genetic correlated with total height and bark thickness. Except for total height, stem diameter and bark thickness, the heritability of all characteristics studied indicated that they are not dependent on environmental conditions.
Keywords: Hevea spp; genetic correlation; phenotypic correlation; inheritance; variances; standard deviation